2014
DOI: 10.1002/jcp.24636
|View full text |Cite
|
Sign up to set email alerts
|

ProbioticL. reuteriTreatment Prevents Bone Loss in a Menopausal Ovariectomized Mouse Model

Abstract: Estrogen deficiency is a major risk factor for osteoporosis that is associated with bone inflammation and resorption. Half of women over the age of 50 will experience an osteoporosis related fracture in their lifetime, thus novel therapies are needed to combat post-menopausal bone loss. Recent studies suggest an important role for gut-bone signaling pathways and the microbiota in regulating bone health. Given that the bacterium Lactobacillus reuteri ATCC PTA 6475 (L. reuteri) secretes beneficial immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
378
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(431 citation statements)
references
References 51 publications
14
378
2
4
Order By: Relevance
“…Intriguingly, treatment of ovx mice with the LGGM partially protected ovx mice from bone loss. The SpaC protein was shown by our research group to be necessary for LGG to 15, and Jam3 in the SI of Conv.R, and GF mice, and in Col.GF mice, following either leuprolide (375 μg/ month) or vehicle control treatment for 10 weeks. (E) Measurement of serum endotoxin levels in mice from experimental groups described in A.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Intriguingly, treatment of ovx mice with the LGGM partially protected ovx mice from bone loss. The SpaC protein was shown by our research group to be necessary for LGG to 15, and Jam3 in the SI of Conv.R, and GF mice, and in Col.GF mice, following either leuprolide (375 μg/ month) or vehicle control treatment for 10 weeks. (E) Measurement of serum endotoxin levels in mice from experimental groups described in A.…”
Section: Discussionmentioning
confidence: 94%
“…This probiotic prevented the increase in CD4 + T cells induced by ovx, secreted anti-TNF factors, and modified microbial communities in the ovx mouse gut (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…L. reuteri suppressed Ovx-induced increases in bone marrow CD4 + T-lymphocytes, which promote osteoclastogenesis, and directly suppressed osteoclastogenesis in vitro. 33 In another study, the addition of L. reuteri prevented TNF-α-mediated suppression of Wnt10b and osteoblast maturation markers in type 1 diabetes (T1D)-induced osteoporosis. 34 In this study, we showed that probiotic treatment protected mice from wear debris-induced osteolysis.…”
mentioning
confidence: 97%
“…They also inhibit Tnfa and Il6 expression and upregulate Il10 in a collagen-induced arthritis model (22) -effects that are likely exerted via NFκB dephosphorylation (23). Importantly, media from the probiotic Lactobacillus is able to decrease both macrophage Tnfa expression and osteoclastogenesis (24,25). Consistent with these findings, Li et al note that probiotic-fed hypogonadal mice display significant decrements in Tnfa and Rankl in both the intestine and BM (7).…”
Section: Resultsmentioning
confidence: 92%